The Double‐Histidine Cu2+‐Binding Motif: A Highly Rigid, Site‐Specific Spin Probe for Electron Spin Resonance Distance Measurements1. (26th March 2015) - Cunningham, Timothy F.; Putterman, Miriam R.; Desai, Astha; Horne, W. Seth; Saxena, Sunil
Abstract The development of ESR methods that measure long‐range distance distributions has advanced biophysical research. However, the spin labels commonly employed are highly flexible, which leads to ambiguity in relating ESR measurements to protein‐backbone structure. Herein we present the double‐histidine (dHis) Cu2+‐binding motif as a rigid spin probe for double electron–electron resonance (DEER) distance measurements. The spin label is assembled in situ from natural amino acid residues and a metal salt, requires no postexpression synthetic modification, and provides distance distributions that are dramatically narrower than those found with the commonly used protein spin label. Simple molecular modeling based on an X‐ray crystal structure of an unlabeled protein led to a predicted most probable distance within 0.5 Å of the experimental value. Cu2+ DEER with the dHis motif shows great promise for the resolution of precise, unambiguous distance constraints that relate directly to protein‐backbone structure and flexibility.